A randomized trial comparing low dose (40 or 80 mg) with standard dose (120 mg) of bacillus Calmette-Guerin for superficial bladder cancer - Vivek Vijjan; Anil Mandhani; Rakesh Kapoor; Deepak Dubey; Aneesh Srivastava; M S Ansari; Pratipal Singh; Anant Kumar (Indian Journal of Urology, 2006)
Objective: Intravesical bacillus Calmette-Guerin (BCG) therapy is considered to be the most effective therapy for high-risk superficial cancer of bladder. Reduction in dose has been tried to decrease the toxicity following instillations of BCG while maintaining efficacy. This study compares the efficacy and toxicity of three different doses of modified Danish 1331 strain of BCG in patients with high risk superficial bladder cancers. Materials and Methods: A prospective randomized study was undertaken between January 2000 to March 2005 to include all patients with superficial bladder cancer who received BCG after fulfilling one or more of the appropriate criteria (grade above 1, stage above Ta, size> 1 cm, multiple or recurrent). One hundred and six patients received 40 mg, 80 mg or 120 mg Danish 1331 strain BCG weekly for six weeks. The recurrence rates, tumor progression, toxicity and long-term outcome of three different doses of BCG were studied. No maintenance therapy was given. Results: Of the 106 patients, 28 received 40 mg, 37 received 80 mg and 41 received 120 mg of intravesical BCG for six weeks. The mean follow-up was three years (range one to six years). Overall, 77.4% patients responded to a single cycle of BCG, with a recurrence rate of 32.1% in 40 mg, 13.5% in 80 mg and 24.3% in the 120 mg groups. Median time to recurrence was seven months, eight months and nine months in the three groups respectively. Overall, six patients (5.6%) developed disease progression, two (7.1%) in the 40 mg, one (2.7%) in the 80 mg and three (7.3%) in the 120 mg arm. Kaplan - Meier analysis for time to recurrence ( P =0.1839) and time to progression ( P =0.595) was not significantly different in the three treatment arms. Adverse effects were seen in 55.6% patients with most being of class 1 severity. Significantly less patients developed severe adverse effects in the 40 mg group as compared to the higher dose groups. Conclusions: We conclude that 40 mg dose of intravesical BCG is as effective as the standard dose in reducing the risk of recurrence and progression. Moreover this dose is associated with significantly less toxicity.